Strategy Implementation: Mckinsey’s 7s Framework Configuration And Performance Of Large Supermarkets In Nairobi, Kenya - Awino, Zachary Bolo; Njeru, Winnie G.; Adwet, Kenneth (Archives of Business Research, 2017)
The study objective was to determine the relationship between strategy implementation of McKinsey’s 7S Framework and performance of large supermarkets in Nairobi. Out of twenty one questionnaires administered, eighteen were received representing a response rate of 86. % and was considered adequate for further analysis. The finding of the study was a correlation coefficient of .868 when the relationship between McKinsey’s 7S and firm performance was tested. This depicts a strong relationship between performance by the firm and the independent variables. The coefficient of determination (R2) was .753. Therefore, McKinsey’s 7S dimensions account for 75.3% of the variations in firm performance. The study sought to assess the influence of Mckinsey’s 7S framework, strategy adoption, barriers to strategy implementation, drivers to strategy implementation and firm performance. The results revealed a correlation coefficient (r) of 0.921 which show a strong relationship between performance by the firm and independent variables. The results showed a R2 of 0.848 was established. The results suggest that strategy adoption, McKinsey 7S framework, drivers to strategy implementation and barriers to strategy implementation account for 84.8% of the variation in firm performance. Factor analysis found that cross-functionality of the strategy adoption, McKinsey 7S framework, drivers to strategy implementation and barriers to strategy implementation as the critical success factors for firm performance. The study concluded that the adoption of Mckinsey’s 7S framework would lead to improved firm performance. Future research work should assess the moderating and intervening effects and incorporate subjective and objective measures of performance.